La Ribot : corpo cero na escena expandida - Romero Baamonde, Maria Eugenia (2019)
The artist La Ribot challenges, with her work, the limits of scenic field while mixing codes from other areas. Moving freely in search of other possible stage performance and other relationship with the public. One of the threads of her work is the presence of her naked body using almost like a blank mold in which she inscribes different identities at his please